Pain Management Competency and its Associated Factors among Nurses - Shrestha, Indu; Payakkaraung, Sudaporn; Sanasuttipun, Wanida (Journal of Nepal Health Research Council, 2023)
Background: Nurses play a vital role to handle the situation in the care of the patients especially for prioritizing and managing care of pain. Nursing competency attributes personal characteristics, professional attitude, values, knowledge and skills to demonstrate professional responsibility through practices. Nursing competency helps to provide high quality essential care to the patients at a right time. This study aimed to explore pain management competency and its associated factors among nurses in a tertiary hospital, Nepal. Methods: A cross- sectional survey with correlational predictive design was conducted with 203 staff nurses who had work experience related to pain for more than two months at Tribhuvan University Teaching Hospital in Nepal. They were working in medical, surgical, gynecology and obstetrics, pediatric and neonatal, emergency and intensive care departments. The participants were selected from inpatient departments by convenience sampling technique from December 2020 to February 2021. SPSS 18.0 version was used for data entry and analysis using descriptive statistics, chi-square and logistic regression. Significant factors reported at P<0.05. Results: In total participants, 67.5% of nurses were competent on pain management. Work experience [OR= 0.426 (95% CI: 0.205-0.887)] could significantly predict on nurses’ competency for pain management. However, there was no significant association educational level, working unit, nurse-physician relationship, and training on nurses’ competency. Conclusions: Based on the findings, two third (67.5%) nurses are competent on pain management and work experience is a factor contributed to the nurses’ competency for pain management, the researcher recommends nurses with lower work experience should provide pre-service training on pain management. Keywords: Competency; nurse; pain management.